'I'd have to fight for my life there': a multicentre qualitative interview study of how socioeconomic background influences medical school choice. Issue 1 (31st December 2022) - Rees, Eliot L; Mattick, Karen; Harrison, David; Rich, Antonia; Woolf, Katherine
ABSTRACT: Students from lower socio-economic backgrounds who were educated in state funded schools are underrepresented in medicine in the UK. Widening access to medical students from these backgrounds has become a key political and research priority. It is known that medical schools vary in the number of applicants attracted and accepted from non-traditional backgrounds but the reasons for this are poorly understood. This study aims to explore what applicants value when choosing medical schools to apply to and how this relates to their socioeconomic background. We conducted a multicentre qualitative interview study, purposively sampling applicants and recent entrants based on socioeconomic background, stage of application and medical school of application. We recruited participants from eight UK medical schools. Participants attended semi-structured interviews. We performed a framework analysis, identifying codes inductively from the data. Sixty-six individuals participated: 35 applicants and 31 first year medical students. Seven main themes were identified; course style, proximity to home, prestige, medical school culture, geographical area, university resources, and fitting in. These were prioritised differently depending on participants' background. Participants from lower socioeconomic backgrounds described proximity to home as a higher priority. This was typically as they intended to be living at home for at least part of the course. Those from higher socioeconomic backgrounds were more concerned with the perceived prestige of medical schools. Since medicine is a highly selective course, only offered at a minority of UK higher education institutions, these differences in priorities may help explain observed differential patterns of medical school applications and success rates by applicant social background.